1973
DOI: 10.1159/000148826
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Regulator for Poliovirus: The Equestron

Abstract: A labile subviral particle (‘the equestron’) is proposed as a multifunctional regulator of poliovirus growth, withaffinities for 45s ribosomal subunits and 5’ ends of viral RNA. These suggested properties suffice to explain suppression of hostprotein synthesis, synchronous synthesis of viral RNA and protein, and timing of maturation. The candidate for the equestron is a precursor to the virionstructural unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1974
1974
1982
1982

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The relative efficiency of translation of host cell mRNA and encephalo myocarditis (EMC) virus RNA has been investigated in cell-free preparations from un infected and EMC virus-infected Krebs-II cells. The ability of cell-free extracts from infected cells to translate exogenously-added EMC virus RNA and total Krebs-II cell mRNA was markedly diminished, but no evidence for the selective inhibition of translation of host cell mRNA in these systems was obtained.Synthesis of host proteins is severely inhibited in cells infected with picornaviruses at a time when virus-specific proteins are actively made [1], It is widely assumed that this inhibition is due to some defect in the initiation of trans lation of host mRNA [2][3][4][5], In this connection, we have studied the ability of extracts prepared from cells infected with encephalomyocarditis (EMC) virus to translate exogenously-added cellular or viral mRNA. Both templates were shown to be translated less efficiently in extracts from infected cells, but no evidence for a selective inhibition of translation of host mRNA was obtained.…”
mentioning
confidence: 99%
“…The relative efficiency of translation of host cell mRNA and encephalo myocarditis (EMC) virus RNA has been investigated in cell-free preparations from un infected and EMC virus-infected Krebs-II cells. The ability of cell-free extracts from infected cells to translate exogenously-added EMC virus RNA and total Krebs-II cell mRNA was markedly diminished, but no evidence for the selective inhibition of translation of host cell mRNA in these systems was obtained.Synthesis of host proteins is severely inhibited in cells infected with picornaviruses at a time when virus-specific proteins are actively made [1], It is widely assumed that this inhibition is due to some defect in the initiation of trans lation of host mRNA [2][3][4][5], In this connection, we have studied the ability of extracts prepared from cells infected with encephalomyocarditis (EMC) virus to translate exogenously-added cellular or viral mRNA. Both templates were shown to be translated less efficiently in extracts from infected cells, but no evidence for a selective inhibition of translation of host mRNA was obtained.…”
mentioning
confidence: 99%
“…Indirect evidence points to additional regulatory roles for the coat proteins, including shutoff of cellular metabolism STEINER-PRYOR and COOPER 1973) and participation in viral RNA synthesis (GHENDON 1972;KORANT 1977 a;). The capsid polypeptides have at least two functional roles; the protection of the viral genome RNA on its way from cell to cell, and the recognition of specific cell receptors present on the plasma membrane.…”
Section: Mapping Of the Viral Genomementioning
confidence: 99%
“…One of the possible explanations may consist in modification of the cellular protein-synthesizing machinery by virus-specific protein(s) in such a way that translation of host cell mRNA is preferentially inhibited. It was suggested, for example, that such a role may be played by the proteins of poliovirus procapsids, VPO, VP 1 and VP 3, after complexing with the smaller ribosomal subunit [2]. In this connection, we have attempted to determine virus-specific proteins bound to the ribosomes of Krebs-II cells infected with encephalomyocarditis (EMC) virus.…”
Section: Introductionmentioning
confidence: 99%
“…Cooper et al [2] reported that some structural polypeptides of poliovirus were associated with the smaller ribosomal subunit. Our preliminary observations also indicate that the relative proportion of different labelled polypeptides bound to the smaller ribosomal subunit from EMC virus-infected cells is not the same as in either whole ribosomes or the larger subunit, the structural polypeptides of the virion being a much more prominent component in the former particles than in the latter.…”
mentioning
confidence: 99%